Egg Yolk Factor of Staphylococcus aureus II. Characterization of the Lipase Activity - Shah, D. B. (1965)
Shah, D. B. (University of Wisconsin, Madison), and J. B. Wilson. Egg yolk factor of Staphylococcus aureus. II. Characterization of the lipase activity. J. Bacteriol. 89:949–953. 1965.—The staphylococcal egg yolk factor was characterized as a lipase. The enzyme had an optimal pH of 7.8, but the optimal pH of stability was 7. Substrate specificity data showed that the relative rate of hydrolysis was lowest with triacetin as substrate, was maximal with tributyrin, and decreased as the chain length of the acyl moieties increased. The enzyme showed an absolute requirement for a fatty acid acceptor like calcium, when the acyl moiety of triglyceride was water-insoluble. Magnesium, strontium, and barium functioned equally well as fatty acid acceptors. The enzyme was able to hydrolyze coconut oil, peanut oil, olive oil, and egg yolk oil.